God, duty and community in English economic life, 1660 - 1720 - Waddell, Brodie (Studies in early modern cultural, political and social history, 2012)
God's will : judgement, providence, and the prayers of the poor -- Oeconomical duties : patriarchy, paternalism, and petitioning -- Communal bonds : solidarity, alterity, and collective action